Quantifying variations in δ18Ow and salinity in modern Bermudan waters on hourly to monthly timescales - Zhang, Jade Z.; Petersen, Sierra V.; Lavis, Shaun; Williams, Bruce (Frontiers in Marine Science, 2024)
Since the mid-1970s, groundwater resources in Bermuda have been explored to supplement growing potable water demand on the island. Much of this work has focused on modeling the shape and size of freshwater lenses beneath the island’s surface, mainly the Devonshire Lens. Less attention has been paid to how these freshwater lenses interact with surrounding coastal seawater, a process that may grow in importance as sea levels rise. Due to isotopic differences between aquifer water and seawater, these interactions can be tracked using the oxygen isotopic composition of water (δ18Ow) samples collected from coastal and subterranean areas. A pilot study found more temporal variation in coastal seawater δ18Ow along Bermuda’s South Shore (the section of the coast closest to the Devonshire Lens) compared to elsewhere around the island and suggested that freshwater was discharging into coastal seawater from the Devonshire Lens in significant quantities. However, this study was limited by its small dataset so could not quantify the full spatial and temporal variability of δ18Ow in this area. Here, we present salinity and δ18Ow measurements from seawater samples collected around Bermuda and in wells tapping the Devonshire Lens on timescales ranging from hourly to monthly to better visualize the dynamic interaction between coastal seawater and aquifer-sourced freshwater. We find tight correlation between salinity and δ18Ow in well waters, indicating a simple linear mixing relationship between seawater and aquifer water in the subsurface. We confirm previous findings of larger variability in δ18Ow along the South Shore compared to elsewhere and relate observed changes to tidal height on hourly to monthly timescales. Surprisingly, South Shore seawater salinity does not vary in accordance with δ18Ow, implying additional mechanisms, such as the addition of salt spray, must be acting to mute salinity changes. These findings also demonstrate the potential in using δ18Ow to study submarine groundwater discharge, as salinity measurements alone did not detect as much variability. As sea levels rise and interactions between ocean and aquifer waters change, coastal and well water δ18Ow measurements may be helpful in tracking these processes, and in particular, changes in aquifer size.